The potential of wind velocity in the Banda Aceh coast to the ability to generate electrical energy by horizontal axis wind turbines - Syuhada, Ahmad; Muhammad Ilham, Maulana; Syahriza, .; Mohd Shahrir, Mohd Sani; Rizalman, Mamat (IOP Publishing, 2020)
The wind is air that moves from a high-pressure area to a low-pressure area. Indonesia has the potential of winds that have speeds ranging from 2 m/s to 6 m/s which blow for a period of 6 hours/day. Many researchers have examined what kinds of problems are in the context of wind turbine energy generation. This study discusses the effect of wind speed and variations in the number of turbine blades on the power generated by horizontal wind turbines to rotate generators, case studies on the coast of Banda Aceh. The windmill used is a horizontal turbine propeller type with 5, 6 and 7 blade variations and made from Meranti wood. Electricity data retrieval is done by pairing the generator, so that the data taken in this measurement is in the form of wind speed data (m/s), speed of rotation of the wheel shaft and generator shaft, and generator voltage (V) and electric current generated. Data collection is carried out for 6 days at 3-9 m/s wind speed. The results showed that for wind speeds below 5 m/s it is more ideal to use a small number of turbines and for wind speeds greater than 7 m/s it is better to use a turbine blade with a large number of blades.